Sociology - Карпчук, Наталія Петрівна; Тихомирова, Євгенія Борисівна; Karpchuk, Nataliia P.; Tykhomyrova, Yevheniia B. (Lesya Ukrainka Eastern European National University, 2018)
Summary of the course : sociology as a science and its place in the humanities and social science. The main functions of sociology. Background of sociology. The place and role of social research in the knowledge of social phenomena. Methods of collecting primary data. The social structure of society. Sociology of work and industrial relations. Sociology of family life and leisure. Sociology of education and culture. Sociology of personality.
Keywords: соціологія; методи соціології; соціальна структура суспільства; соціологія праці; соціологія відпочинку; соціологія освіти; соціологія сім'ї; соціологія культури; соціологія релігії; sociology; methods of sociology; social structure of society; sociology of work; sociology of leisure; sociology of education; sociology of family; sociology of culture; sociology of religion